Parasitic helminths of the freshwater neotropical fish Hoplias malabaricus (Characiformes, Erythrinidae) from South America basins - ROCHA, Carlos Alberto Machado da (Taylor and Francis Group, 2022)
This study gathered the largest amount of evidence available concerning the presence of helminths in the Hoplias malabaricus species (Trahira, tra ́ıra in Portuguese) from limnic ecosystems in South America. At least 18 species of helminths belonging to 15 genera, 14 families, 10 orders, and 8 classes were found. The greatest diversity of parasitic species was observed among the Digeneans and acanthocephalus. Throughout the text, helminths are presented in four sections corresponding to their phyla: Platyhelminthes, Acanthocephala, Nematoda, and Annelida. The different niches occupied by the Trahira in the heteroxenic helminth cycles are also analyzed, verifying whether this fish acts as an intermediate or a definitive host.